Algebraic fields and the dynamical approach to physical geometry - Menon, T (University of Chicago Press, 2019)
Brown and Pooley’s ‘dynamical approach’ to physical theories asserts, in opposition to the orthodox position on physical geometry, that facts about physical geometry are grounded in, or explained by, facts about dynamical fields, not the other way round. John Norton has claimed that the proponent of the dynamical approach is illicitly committed to spatiotemporal presumptions in ‘constructing’ spacetime from facts about dynamical symmetries. In this paper, I present an abstract, algebraic formulation of field theories and demonstrate that the proponent of the dynamical approach is not committed, in special relativity, to the illicit presumptions to which Norton refers.